Cyclooxygenase-2 inhibitors and free flap complications after autologous breast reconstruction: A retrospective cohort study. Issue 11 (November 2017) - Bonde, Christian; Khorasani, Hoda; Hoejvig, Jens; Kehlet, Henrik
Summary: Background: A key component of modern analgesics is the use of multimodal opioid-sparing analgesia (MOSA). In the past, our analgesic regime after autologous breast reconstruction (ABR) included either NSAID or a selective cyclooxygenase-2 (COX-2) inhibitor. COX-2 inhibitors are superior to NSAIDs because of the well-known side effects of NSAID treatment (bleeding/gastrointestinal ulcers). However, COX-2 inhibitors have been suggested to increase flap failure rates. We report our experience in using COX-2 inhibitors as part of our post-operative MOSA after ABR using free flaps. Materials and methods: A total of 132 unilateral secondary ABR were performed (DIEP or MS-TRAM) in the NSAID period (2007–2011) and 128 in the COX-2 inhibitor period (2006, 2012–2014). The same surgical team operated all patients. Data were collected prospectively and reviewed to compare the two periods, with special focus on reoperations due to bleeding/haematomas and flap thrombosis/failure. Comparisons between the COX-2 inhibitor and NSAID were made. Results: Median age, ischaemia time, blood loss and operating time were similar in the two periods. Significantly, more patients were re-operated because of post-operative haematoma in the NSAID group (n = 13/132, 9.8%) than in the COX-2 inhibitor group (n = 4/128, 3.1%) (p = 0.02). We found no difference in flap loss rates between the NSAID (n = 2/132, 1.5%) and the COX-2 inhibitor groups (n = 3/128, 2.3%) (p = 0.63). No patients suffered from thromboembolic complications or gastrointestinal bleeding. Conclusions: Multimodal analgesia using a COX-2 inhibitor is safe in ABR with free flaps and does not increase flap failure. COX-2 inhibitors seem superior to NSAID with reduced risk of post-operative haematomas.